Unilateral Phthiriasis Palpebrarum Infestation: A Rare Presentation - Kamble, Vinit Kumar; Gupta, Sharad; Yadav, Reena; Singh, Sanjay Kumar; Bista, Bipin; Sah, Nirajan (Journal of Lumbini Medical College, 2020)
Introduction: Phthiriasis palpebrarum is an uncommon eyelid infestation mainly caused by Phthirus pubis also known as crab lice. Case report: A 16 years male presented with redness, itching and watering of the right eye for one week. On slit-lamp biomicroscopic examination lice and nits anchored to the eyelashes along with seborrheic material accumulation was noted. Lice, partial nits along with matted eyelashes were removed and sent to laboratory for microscopic examination. On follow up visit remaining nits were expunged. Conclusion: Meticulous slit lamp biomicroscopic examination should be done in all patients presenting with itching of the eyelids in conjunction with clinical findings resembling seborrhea and evidence for Phthiriasis palpebrarum should be looked for.